Differentiation of Low-Grade and High-Grade Glioma Using the Combination of Conventional Magnetic Resonance Imaging and Apparent Diffusion Coefficient Value - Rahmad Mulyadi; Mochammad Hatta; Andi Asadul Islam; Bachtiar Murtala; Jumraini Tammase; Reninda Ananda Aman; Eka Susanto (The Indonesian Biomedical Journal, 2020)
BACKGROUND: The conventional magnetic resonance imaging (cMRI) and apparent diffusion coefficient (ADC) may have a role in predicting tumor grade for gliomas and may in turn assist in identifying tumor biopsy sites. In this study, we aimed to determine the added value of a joint approach of diffusion-weighted imaging (DWI) and cMRI to determine of low grade and high-grade glioma, compare to cMRI alone.METHODS: Data were collected from 56 glioma patients, who underwent examinations and received treatment at Cipto Mangunkusumo National Central General Hospital, Jakarta, Indonesia, from the period of 2015–2018. Inclusion criteria was patients who underwent cMRI with a DWIADC sequence and patient that were diagnosed with glioma according to the histopathological results. Pathology reports of the imaging results were reviewed independently. A receiver operator curve (ROC) analysis assessed the predictive potential of cMRI and ADC values for low-grade and high-grade gliomas.RESULTS: Fifty-six subjects met the inclusion criteria. The combination of MRI and ADC values increased sensitivity (to 90%) and negative predictive value (to 92.9%), and also improved the negative likelihood ratio (to 0.14). However, the combination of MRI and ADC values had the highest area under the curve (78.6%) and sensitivity (78.6%), which was similar to the separated examination.CONCLUSION: The combination of ADC value and conventional MRI increases sensitivity in differentiating low-grade and high-grade glioma compared to separated examination.KEYWORDS: glioma, conventional MRI, ADC value